Back Cover: Electrochemical Oxidation of Organotrifluoroborate Compounds (ChemElectroChem 12/2016). Issue 12 (22nd November 2016) - Suzuki, Junji; Tanigawa, Masahiro; Inagi, Shinsuke; Fuchigami, Toshio
Abstract : The Back Cover picture shows that the anodic oxidation of an organic trifluoroborate successfully generates its radical and cationic species for further chemical reactions. More information can be found in the Article by T. Fuchigami and co‐workers onpage 2078 in Issue 12, 2016 (DOI:10.1002/celc.201600451 ).